2018
DOI: 10.1259/bjr.20180585
|View full text |Cite
|
Sign up to set email alerts
|

Improving diagnostic accuracy in clinically ambiguous paediatric appendicitis: a retrospective review of ultrasound and pathology findings with focus on the non-visualised appendix

Abstract: Ultrasound has the potential to improve diagnostic accuracy in clinically ambiguous appendicitis. Advances in knowledge: This paper furthers the evidence on the efficacy of ultrasound as a diagnostic tool in acute appendicitis in children, especially when the diagnosis is clinically equivocal. It also sheds further light on the "non-visualized appendix" with almost half of these patients having pathologically confirmed appendicitis; meaning advanced imaging with CT or MR may be indicated in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Kelly et al reported in their study that 983 appendectomies were performed of whom only 189 had preoperative ultrasound, and the rest of the patients (80.7%) had no imaging modality. 19 The rate of negative appendectomy is remarkably higher than the literature in this study. The overall negative appendectomy rate is 32%, and this rate rises to 46% within the clinically equivocal group that underwent ultrasound.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Kelly et al reported in their study that 983 appendectomies were performed of whom only 189 had preoperative ultrasound, and the rest of the patients (80.7%) had no imaging modality. 19 The rate of negative appendectomy is remarkably higher than the literature in this study. The overall negative appendectomy rate is 32%, and this rate rises to 46% within the clinically equivocal group that underwent ultrasound.…”
Section: Discussioncontrasting
confidence: 50%
“…Kelly et al reported in their retrospective study overall, the sensitivity of ultrasound for AA (used in 19% of cases as the first-line imaging) was 72.55% and specificity was 77.01% 19. In our study, "surgeon prediction + US" was used in 70.4% of the study cohort, and US sensitivity and specificity were 62.4% and 57.9%, respectively.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…Ultrasound was utilized frequently in the paediatric population at SWHC. Though a useful tool in the diagnosis of appendicitis, low‐volume centres have demonstrated significant non‐concordance between sonographic and pathological findings 36 . We observed a false positive rate of 34%.…”
Section: Discussionmentioning
confidence: 61%
“…(13,14) Most studies do not recommend age cutoffs for maximum cecal appendix diameter in US diagnosis of appendicitis. (15,16) On top of allowing detailed understanding of abdominal anatomy by virtual dissection, US complies with the ALARA (As Low As Reasonable Achievable) principle, (17) which expresses concern regarding diagnostic imaging and sets standards for use of lowest amounts of radiation. This principle supports the applicability of ultrasonography as a non-ionizing imaging modality that should have priority for abdominal assessment in urgent cases.…”
Section: ❚ Discussionmentioning
confidence: 99%